FUNGSI SEKTOR UNGGULAN INDUSTRI TERHADAP PERTUMBUHAN EKONOMI DELI SERDANG - Muhammad Nasir (Quantitative Economics Journal, 2017)
Deli Serdang area surrounds the capital of North Sumatra Medan, there are industrial concentration of industrial concentration in Sunggal sub-district, Tanjung Morawa sub district, Percut Sei Tuan sub-district, on the other side of industry sector contribute greatly to society prosperity level of Deli Serdang which is 32,12%. The problem is how much influence the industrial sector has on the economic growth in Deli Serdang. The purpose of this study to determine the magnitude of the influence of industrial sector on economic growth Deli Serdang. The industrial sector has a value of LQ> 1 means the industrial sector is a leading sector for Deli Serdang. To know the magnitude of industrial sector influence on the economic growth, linear regression model is used. This study uses time series data from 1993-2015 taken from BPS North Sumatra. The result of analysis shows that 15% of economic growth variation can be explained by industry sector while 85% is explained by other independent variable which is not included in research model. The value of these negative constants shows that without the leading sector of the industry the economic growth in deli serdang decreases. The estimation result of Deli Serdang's economic growth function is influenced by the industry's leading sectors having a positive and significant influence with 95% confidence level.